Enhanced Performance of Aqueous Sodium‐Ion Batteries Using Electrodes Based on the NaTi2(PO4)3/MWNTs–Na0.44MnO2 System. Issue 8 (25th July 2014) - Pang, Gang; Nie, Ping; Yuan, Changzhou; Shen, Laifa; Zhang, Xiaogang; Zhu, Jiajia; Ding, Bing
Abstract Sodium‐ion batteries with good electrochemical performance are of great significance for grid‐scale energy storage applications. Herein, an aqueous rechargeable Na‐ion battery has been fabricated with multiwalled carbon nanotube (MWNT)‐containing NaTi2(PO4)3/MWNTs nanocomposites as the anode and Na0.44MnO2 nanorods as the cathode in a 1 M aqueous Na2SO4 electrolyte and the device was carefully studied. Owing to the open framework structures (containing large interstitial sites) that both NaTi2(PO4)3 and Na0.44MnO2 possess, the fast Na‐ions will facilitate free transport. Benefiting from their unique structural features, the aqueous battery system exhibited an average charge and discharge voltage of approximately 1.1 V, a high energy density of 58.7 Wh kg−1 in terms of total electroactive materials, and could deliver a reversible capacity of approximately 50 mAh g−1 after 300 cycles at 2 C rate; the corresponding coulombic efficiency was nearly constant at approximately 95 %. These results, together with the safety and cost perspectives of aqueous electrolytes indicated that the aqueous Na‐ion battery may be a good candidate for safe, inexpensive, high‐power energy storage systems.